2020
DOI: 10.1073/pnas.1917060117
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa lacking Fertilization Influencing Membrane Protein (FIMP) fail to fuse with oocytes in mice

Abstract: Sperm–oocyte fusion is a critical event in mammalian fertilization, categorized by three indispensable proteins. Sperm membrane protein IZUMO1 and its counterpart oocyte membrane protein JUNO make a protein complex allowing sperm to interact with the oocyte, and subsequent sperm–oocyte fusion. Oocyte tetraspanin protein CD9 also contributes to sperm–oocyte fusion. However, the fusion process cannot be explained solely by these three essential factors. In this study, we focused on analyzing a testis-specific ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 54 publications
4
74
0
Order By: Relevance
“…Hence, the transmembrane domain may be important for the normal functioning of TMEM95 in underpinning sperm−oocyte fusion. The necessity of the transmembrane domain in fusion-related sperm factors has also been demonstrated in FIMP (31). The impaired fusion ability of Fimp KO spermatozoa is restored by Tg expression of the membrane isoform of FIMP.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Hence, the transmembrane domain may be important for the normal functioning of TMEM95 in underpinning sperm−oocyte fusion. The necessity of the transmembrane domain in fusion-related sperm factors has also been demonstrated in FIMP (31). The impaired fusion ability of Fimp KO spermatozoa is restored by Tg expression of the membrane isoform of FIMP.…”
Section: Discussionmentioning
confidence: 88%
“…While a combination of IVF and fusion-inhibiting antibodies had nominated critical proteins, IZUMO1 was, until now, the only sperm protein proven to be essential by KO mouse studies (2,4). Recently, by making KO mice using the CRISPR-Cas9 system, we identified sperm protein FIMP as a sperm−oocyte fusion-related protein (31). Specifically, FIMP localizes to the equatorial segment of acrosome-intact spermatozoa, and a faint signal remains after the acrosome reaction in some spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggesting that ZP3 and/or glycans are the ZP sperm receptor has also been obtained [35]; however, targeted gene deletion experiments in animal models did not settle the question because ZP2 and ZP3 are necessary for the formation of the ZP [29,36]. Notably, none of the new essential sperm proteins seem to be involved in ZP binding, as removal of the ZP does not overcome the infertility defect of gene-deleted sperm [25][26][27][28]. The crystal structure of ZP proteins might finally provide the long-awaited answer, and a recent structure of the ZP domain, a protein polymerisation module of approximately 260 amino acids found in many secreted proteins including all ZPs, suggests that the sperm-binding region might lie at the interface between the ZP2 and ZP3 subunits [37].…”
Section: How Does the Sperm Recognise The Zp?mentioning
confidence: 99%
“…The introduction of gene editing technologies in the 1980s represented an invaluable tool to investigate gene functions in model organisms [21], and the remarkable advances made over the last decade [22] have made the creation of gene-deficient mice much easier and have been systematically applied to investigate the role of a large number of potential sperm candidates, many of which were found to have no role in fertility [23,24]. Remarkably, in just a few months, 4 new genes that encode sperm cell surface or secreted proteins have been reported that are essential for male fertility: SPerm ACrosome membrane-Associated protein 6 (Spaca6), Fertilisation Influencing Membrane Protein (Fimp), Sperm-Oocyte Fusion required 1 (Sof1), and TransMEMbrane protein 95 (Tmem95) [25][26][27][28]. In this article, we will discuss 2 fundamental and yet enduring mysteries concerning sperm-egg recognition and place these recent discoveries into our understanding of fertilisation.…”
Section: Introductionmentioning
confidence: 99%